Subchronic Exposure to Environmental Concentrations of Chlorpyrifos Affects Swimming Activity of Rainbow Trout Larvae. (17th September 2021) - Weeks Santos, Shannon; Gonzalez, Patrice; Cormier, Bettie; Mazzella, Nicolas; Moreira, Aurélie; Clérandeau, Christelle; Morin, Bénédicte; Cachot, Jérôme
Abstract: Chlorpyrifos (CPF), an organophosphorous pesticide, can be found in aquatic ecosystems at concentrations of up to several hundred nanograms per liter because of water runoff from treated crops. While some studies have shown that low concentrations of CPF may have adverse effects on aquatic species, comparatively little is known about its effect on fish embryos and larvae. To investigate the developmental effects of CPF, rainbow trout ( Oncorhynchus mykiss ) eyed‐stage embryos were exposed in semistatic conditions to 0.3 and 3 µg/L of CPF up to the end of the sac‐fry stage, 3 weeks, at 12 °C. Several endpoints were analyzed including survival, hatching delay, hatching success, biometry, swimming activity, DNA damage, lipid peroxidation, protein carbonyl content, acetylcholinesterase (AChE) activity, and gene expression. At the end of the 3‐week exposure, larvae exposed to the highest concentration of CPF were less mobile compared to the control and the lowest CPF conditions. No significant differences in AChE activity were observed in either set of CPF conditions compared to control, but it was significantly reduced for larvae exposed to 3 µg/L compared to those exposed to 0.3 µg/L of CPF. Expression of genes that encoded estrogen receptor beta was downregulated for larvae exposed to both CPF concentrations. Expression of cytochrome P450 family 19 subfamily A member 1 was also significantly repressed but only on larvae exposed to the highest concentration of CPF. Our results indicated that subchronic exposure to environmental concentrations of CPF could lead to sublethal effects on early‐life stages of rainbow trout, especially effects on swimming activity that could affect foraging activity and escaping from predators. Environ Toxicol Chem 2021;40:3092–3102. © 2021 SETAC